Mesoporous Titanium Nitride‐Enabled Highly Stable Lithium‐Sulfur Batteries. Issue 32 (27th May 2016) - Cui, Zhiming; Zu, Chenxi; Zhou, Weidong; Manthiram, Arumugam; Goodenough, John B.
Abstract : The TiN–S composite cathode exhibits superior performance because of higher electrical conductivity and the capture of the soluble intermediate species of the electrode reactions by 2–5 nm mesopores and strong N–S surface bonding.